Mollo’s Women Nurturing Body and Nature: Aleta Baun, Nifu Ideology and Mutis Mountain - Desintha D. Asriani (Yayasan Jurnal Perempuan, 2015)
This article focuses on women’s experiences regarding issue of resources governance. It is strongly related to the emergence of mining which proved to be destructive to nature’s and woman’s interests. Through the years the mining has deteriorated the life of women such as threatening food security and women’s sexual and reproductive health and rights. Molo woman’s experiences depict risks that must be faced when the logic of resource governance is dominated by exploitative powers. In addition, stories of Molo women exposed the dynamic of survival and ideas to place the movement in sustainable way.